Low-Fat Nondairy Minidrink Containing Plant Stanol Ester Effectively Reduces LDL Cholesterol in Subjects with Mild to Moderate Hypercholesterolemia as Part of a Western Diet. (16th September 2013) - Hallikainen, Maarit; Olsson, Johan; Gylling, Helena
Abstract : The cholesterol-lowering efficacy of plant stanol ester (STAEST) added to fat- or milk-based products is well documented. However, their efficacy when added to nondairy liquid drinks is less certain. Therefore, we have investigated the cholesterol-lowering efficacy of STAEST added to a soymilk-based minidrink in the hypercholesterolemic subjects. In a randomized, double-blind, placebo-controlled parallel study, the intervention group (n = 27 ) consumed 2.7 g/d of plant stanols as the ester in soymilk-based minidrink (65 mL/d) with the control group (n = 29 ) receiving the same drink without added plant stanols once a day with a meal for 4 weeks. Serum total, LDL, and non-HDL cholesterol concentrations were reduced by 8.0, 11.1, and 10.2% compared with controls (P < 0.05 for all). Serum plant sterol concentrations and their ratios to cholesterol declined by 12–25% from baseline in the STAEST group while the ratio of campesterol to cholesterol was increased by 10% in the controls (P < 0.05 for all). Serum precursors of cholesterol remained unchanged in both groups. In conclusion, STAEST-containing soymilk-based low-fat minidrink consumed once a day with a meal lowered LDL and non-HDL cholesterol concentrations without evoking any side effects in subjects consuming normal Western diet. The clinical trial registration number isNCT01716390 .